2014
DOI: 10.1155/2014/415868
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of Utilizing a Smartphone Based Application to Monitor Outpatient Discharge Instruction Compliance in Cardiac Disease Patients around Discharge from Hospitalization

Abstract: The purpose of this study was to determine the feasibility and acceptability of utilizing a smartphone based application to monitor compliance in patients with cardiac disease around discharge. For 60 days after discharge, patients' medication compliance, physical activity, follow-up care, symptoms, and reading of education material were monitored daily with the application. 16 patients were enrolled in the study (12 males, 4 females, age 55 ± 18 years) during their hospital stay. Five participants were rehosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 20 publications
0
44
0
Order By: Relevance
“…In a 90-day study of sleep disturbance in 30 patients with breast cancer, the overall compliance rate for daily data entry following a push notification was 45% [20]. A 2-month study using smartphones to examine compliance in patients with cardiac disease following hospital discharge recruited 11 patients, only 4 of whom completed data entry beyond 31 days [21]. Thus, our results show better ongoing engagement than other studies in the limited literature on smartphone collection of longitudinal self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…In a 90-day study of sleep disturbance in 30 patients with breast cancer, the overall compliance rate for daily data entry following a push notification was 45% [20]. A 2-month study using smartphones to examine compliance in patients with cardiac disease following hospital discharge recruited 11 patients, only 4 of whom completed data entry beyond 31 days [21]. Thus, our results show better ongoing engagement than other studies in the limited literature on smartphone collection of longitudinal self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Smartphone for home rehabilitation exercises just started since these tools are now available to the largest number in developed countries. It was firstly studied for cardiac disease [ 57 , 58 ], pulmonary rehabilitation [ 59 ], or prevention of ankles sprains [ 60 , 61 ].…”
Section: Using Smartphone For Proprioception Rehabilitation In Autmentioning
confidence: 99%
“…34 A study of 62 male patients in Poland undergoing CR after acute MI also showed that a home-based program, with remote ECG monitoring and a mobile device with preprogrammed exercise instructions, showed similar benefit in physical capacity compared to traditional CR. 59 Several small studies have also supported the feasibility of various mHealth applications in the setting of CR, with success in monitoring medication adherence, 13,21 estimating levels of physical activity, 60 and providing real-time data to clinicians for feedback. 33 Notably, older adults in these studies did not report difficulty using the mHealth technology.…”
Section: Mhealth In Crmentioning
confidence: 99%
“…26 As the population ages and CVD becomes more common, these types of mHealth applications could be of particular utility in older adults. A list of selected studies 11,[13][14][15][16][17][18]20,21,23,24,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] regarding mHealth in this domain that may be relevant to older adults is provided in Table 1. The remainder of this narrative review will focus on mHealth cardiac rehabilitation (mHealth-CR) in older patients, which represents a particularly attractive target for intervention.…”
Section: Applications Of Mhealth In Older Adults: An Overviewmentioning
confidence: 99%